Analisis Fikih Lingkungan Mengenai Tindak Pidana Dalam Pasal 68 Huruf (A) UU No. 17 Tahun 2019 Tentang Sumber Daya Air - Baihaqi, Achmad (Institut Agama Islam Negeri Ponorogo, 2022)
The public interest is very oriented to the benefit and refuses damage to the community, nation and state from environmental damage, especially water which is very important for people's lives. 17 of 2019 which states